Welcome to the new Editor-in-Chief - Godoy-Santos, Alexandre Leme (Journal of the Foot & Ankle, 2023)
With great enthusiasm, we welcome the new Editor-in-Chief of the Journal of the Foot and Ankle, Prof. Dr. Caio Nery. On behalf of the entire editorial team and the scientific community, we would like to express our sincere joy at having him in such an important position. His nomination as Editor-in-Chief is undoubtedly a reflection of his outstanding career and significant contributions to medicine and foot and ankle specialty. His vast knowledge and experience, combined with his passion for scientific research, will certainly further strengthen the reputation and impact of our prestigious journal. We hope his leadership will bring new perspectives and opportunities to the Journal of the Foot and Ankle, further enriching its content and promoting the dissemination of high-quality scientific information. ABTPé is committed to supporting him in all his initiatives and working together to maintain the high standards of excellence for which our journal is known. Once again, welcome, Prof. Dr. Caio Nery. We are sure that your leadership will be inspiring and that we will continue to advance towards the indexing of our journal. Best regards, Alexandre Leme Godoy-Santos Elected President ABTPé (2024–2025) Emeritus Editor of the Journal of the Foot and Ankle